Terra RoZa . Think Pink - Tardozzi, Aldo
Duration: 00:20:00 Many people have "pink dreams" but only two of them tried to paint their reality in pink. Tito and Brankica are taking us into a world full of pink paintings, dresses, furniture and walls that separate them from the "un-pink" world. But, despite this "cover-up", one has to wonder: is their life pink perfect...or maybe not? The film was shot as part of the Documentary Workshop / Imaginary Academy in Groznjan, Croatia.